The Exosomes Containing LINC00461 Originated from Multiple Myeloma Inhibit the Osteoblast Differentiation of Bone Mesenchymal Stem Cells via Sponging miR-324-3p. (25th January 2022) - Wu, Yang; Zhang, Zhemei; Wu, Jing; Hou, Jinxia; Ding, Guosheng
Abstract : Multiple myeloma is one of the hematological malignancies and inhibited osteoblast differentiation of bone marrow mesenchymal stem cells (BM-MSCs) which has been proved as a major complication of the patients with multiple myeloma. However, the pathomechanism of symptom remains unclear. Besides, several studies have indicated that LINC00461 plays an important role in the progression of multiple tumors. Hence, this study attempted to reveal the role of LINC00461 in the osteoblast differentiation of MSCs. In this study, the expression level of LINC00461 in the exosomes of multiple myeloma cells was measured, and BM-MSCs were cultured with the exosomes to observe the change of cellular phenotype. Moreover, downstream target of LINC00461 was searched and verified with dual-luciferase reporter assay, and the activation of the Wnt/ β -catenin pathway was also observed by Western blot. The results showed that the isolated BMSCs exhibited special biomarkers of MSCs. LINC00461 was significantly upregulated in the exosomes originated multiple myeloma cells, and increased LINC00461 significantly impeded the osteoblast differentiation of MSCs. Moreover, LINC00461 could significantly suppress the activation of the Wnt/ β -catenin pathway in MSCs. In conclusion, this study suggested that LINC00461 in exosomes of multiple myeloma could reduce the activity of the Wnt/ β -catenin pathway to inhibit the osteoblast differentiation of BM-MSCs via targeting miR-324-3p.